2021
DOI: 10.1155/2021/6632469
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Related Risk Factors of Intestinal Parasitosis among Private School-Going Pupils of Dharan Submetropolitan City, Nepal

Abstract: Introduction. Intestinal parasitic infections are most common and prevalent among children and accounts for great morbidity and mortality. Objective. This research is aimed at studying the prevalence and related risk factors of parasitic infections among private school-going pupils of Dharan Submetropolitan City. Methods and Materials. This was a cross-sectional laboratory-based study conducted from 13 November 2018 to 26 February 2019 among 400 private school pupils. The stool samples were collected and micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
2
0
3
Order By: Relevance
“…Del total de 801 niños, 153 presentaron algún tipo de parasitosis intestinal, con lo cual se estimó una prevalencia de 19.1% IC 90% 16.5-21.9. Esta prevalencia fue 3.2% más frecuente en varones (20.7, IC 90% 17-24) en comparación con las mujeres (17.5, IC 90% [14][15][16][17][18][19][20][21].…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Del total de 801 niños, 153 presentaron algún tipo de parasitosis intestinal, con lo cual se estimó una prevalencia de 19.1% IC 90% 16.5-21.9. Esta prevalencia fue 3.2% más frecuente en varones (20.7, IC 90% 17-24) en comparación con las mujeres (17.5, IC 90% [14][15][16][17][18][19][20][21].…”
Section: Resultsunclassified
“…Al analizar las prevalencias en relación con el estado nutricional (Figura 2), se determinó que fue mayor en los niños desnutridos (85.7% IC 90% 67-96) que en los de peso normal (16.1% IC 90% [14][15][16][17][18][19]. Además, en los niños con sobrepeso y obesidad la prevalencia fue un poco mayor que en los de peso normal (22.5% IC 90% 15-32 y.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…64 This study reported that the rate of parasitic infection was significantly more among under-five children who were not taking antiparasitic drugs compared to those children who received the antiparasitic drug (AOR = 2.4; 95% CI: 1.34-5.62) his study was supported by a study conducted in Nepal. 65 This might be a result of the antiparasitic medication reducing the number of worms in their bodies. 66…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal worms have been associated with socio-economic status, and poor environmental and personal hygiene [10,11]. Additionally, negligence in mass deworming programmes, lack of awareness and cultural practices have been reported to contribute to continued infection transmission and reinfection [12]. In developing countries, periodic deworming with Albendazole, Pyrantel pamoate, Mebendazole and other Anthelminths was effective for the treatment of intestinal worm infection [13,14].…”
Section: Introductionmentioning
confidence: 99%